2022
DOI: 10.1016/j.eurox.2021.100140
|View full text |Cite
|
Sign up to set email alerts
|

Differences in maternal soluble ST2 levels in the third trimester of normal pregnancy versus preeclampsia

Abstract: Background Preeclampsia is associated with intense inflammatory response in pregnancy, and soluble ST2 (sST2) is pathologically increased in this condition. No data exist regarding maternal sST2 levels in normal pregnancy versus preeclampsia in areas of southeast Asia with an ethnic Malay predominance. Materials and Methods Patients were sorted into normal pregnancy or preeclampsia. Patients with a history of allergic, inflammatory, or malignant disease were excluded. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
2
2
Order By: Relevance
“…found that mean sST2 level in the PE group (85.89 ng/ml) was significantly higher than the control group mean (38.3 ng/ml) during the third trimester (30-38 weeks) in singleton pregnancies. 12 The median of sST2 in the PE group in our study was lower than in the previous study focused on singleton pregnancies that further explained the different pathogenesis of PE in twin pregnancies. Additionally, Stampalija T et al 13 found that serum sST2 concentration in singleton pregnant women with PE was higher than that in normal pregnant women, especially in preterm and severe PE.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…found that mean sST2 level in the PE group (85.89 ng/ml) was significantly higher than the control group mean (38.3 ng/ml) during the third trimester (30-38 weeks) in singleton pregnancies. 12 The median of sST2 in the PE group in our study was lower than in the previous study focused on singleton pregnancies that further explained the different pathogenesis of PE in twin pregnancies. Additionally, Stampalija T et al 13 found that serum sST2 concentration in singleton pregnant women with PE was higher than that in normal pregnant women, especially in preterm and severe PE.…”
Section: Discussioncontrasting
confidence: 70%
“…Sasmaya PH et al. found that mean sST2 level in the PE group (85.89 ng/ml) was significantly higher than the control group mean (38.3 ng/ml) during the third trimester (30–38 weeks) in singleton pregnancies 12 . The median of sST2 in the PE group in our study was lower than in the previous study focused on singleton pregnancies that further explained the different pathogenesis of PE in twin pregnancies.…”
Section: Discussioncontrasting
confidence: 66%
“…33 Disfungsi endotel yang terjadi pada preeklamsia 34 sST2 sebagai biomarker kerusakan miokardium tampak meningkat secara bermakna pada preeklamsia, terutama pada preeklamsia dengan komplikasi. 35,36 Terdapat korelasi positif antara sST dengan kejadian preeklamsia awitan dini dimana secara klinis gangguan organ-organ tampak lebih berat termasuk kerusakan miokardium. Pemeriksaan sST2 dapat digunakan pula untuk mengetahui keadaan disfungsi miokardium subklinis pada pasien riwayat preeklamsia.…”
Section: Biomarker Sst2 Sebagai Penanda Kerusakan Kardiovaskular Pada...unclassified
“…The study's p-value of 0.010 < 0.05 means a relationship between exposure to cigarette smoke and the incidence of hypertension in pregnant women (Sasmaya et al, 2022). Results mean that pregnant women exposed to cigarette smoke are 3.5 times more likely to suffer from hypertension than pregnant women who are not exposed to cigarette smoke (Sibai et al, 2021).…”
Section: Figure 5 Progress Of Triglicerides Valuesmentioning
confidence: 99%
“…In pregnant women, calcium is needed more because it is a substitute for the reserve of tissue formation in the fetus. So that if pregnant women lack calcium can increase the risk of hypertension four times (Sasmaya et al, 2022).…”
Section: Figure 5 Progress Of Triglicerides Valuesmentioning
confidence: 99%